2017
DOI: 10.1038/s41467-017-01044-y
|View full text |Cite|
|
Sign up to set email alerts
|

Triparental plants provide direct evidence for polyspermy induced polyploidy

Abstract: It is considered an inviolable principle that sexually reproducing organisms have no more than two parents and fertilization of an egg by multiple sperm (polyspermy) is lethal in many eukaryotes. In flowering plants polyspermy has remained a hypothetical concept, due to the lack of tools to unambiguously identify and trace this event. We established a high-throughput polyspermy detection assay, which uncovered that supernumerary sperm fusion does occur in planta and can generate viable polyploid offspring. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 39 publications
(36 reference statements)
2
32
0
Order By: Relevance
“…Whether rare natural instances of triparental polyploidy due to break down of the egg cell polyspermy barrier are an important mode of speciation, as Nakel et al propose [8], remains to be shown. Polyploidization is considered a major driver of plant evolution, as up to 70% of flowering plant species are of polyploid origin [14].…”
Section: Current Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Whether rare natural instances of triparental polyploidy due to break down of the egg cell polyspermy barrier are an important mode of speciation, as Nakel et al propose [8], remains to be shown. Polyploidization is considered a major driver of plant evolution, as up to 70% of flowering plant species are of polyploid origin [14].…”
Section: Current Biologymentioning
confidence: 99%
“…Meanwhile, Rita Groß-Hardt's group set up an independent system they call high-throughput polyspermy detection (HIPOD) to show that polyspermy results in viable polyploids in Arabidopsis at a rate of 0.012% [8]. In their approach, only seedlings inheriting a GAL4 driver and a UAS target from two independent sperm cells can survive herbicide selection.…”
Section: Current Biologymentioning
confidence: 99%
“…In natural and cultivated populations of flowering plants, however, polyspermy has long remained a hypothetical concept because tools to detect naturally occurring polyspermy in higher plants have been lacking (Tekleyohans, Mao, Kägi, Stierhof, & Groß-Hardt, 2017). A recent breakthrough in experimental techniques has confirmed the production of progenies consisting of one mother and two fathers via heteropollination (-fertilization) in Arabidopsis (Nakel et al, 2017).…”
Section: How Do Triploids Emerge Via Polyspermy?mentioning
confidence: 99%
“…In contrast to animals, polyspermic zygotes of angiosperms can undergo nuclear/cell division and embryonic development with subsequent development into triploid plants (Toda, Ohnishi, & Okamoto, ). Furthermore, triparental progenies can be produced via heteropollination derived possible polyspermy in plants (Nakel et al, ). These reports all indicate that the emergence of triploid progenies via polyspermy among diploid populations is a significant factor in polyploidization, speciation and plant evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Such technique provides a powerful tool to study developmental profiles of polyspermic zygotes, embryos, and plants (reviewed by Toda et al in this issue). To address naturally occurring polyspermy events, Nakel et al () took advantage of the GAL4/UAS two‐component system adapted from yeast. Their high‐throughput polypaternal breeding design comprises of one plant line containing the GAL4 transcription factor under a ubiquitous promoter and a second plant line containing the GAL4 responsive UAS enhancer driving a YFP ‐tagged herbicide resistance gene.…”
Section: Plant Polyspermy: Milestones and Challengesmentioning
confidence: 99%